(3GdbGfhf GdeOfj, GdYbhO GdNGUI GdeOfjI hGdJLGQjIs - (3HjfGHfJ(B, (3BdGfs ((3dHfGfs (3GdeDSSI GdLGeYjI ddOQGSGJs, 2004)
(3OQGSI GdYbhO GdNGUI GdeOfjI hGdJLGQjI, hgj GeJOGO WHjYj ddfXQjI GdYGeI ddehLHGJ, JbqOe EYeGdgG aj eNJda GdbWGYGJ GdGbJUGOjI(B. (3hgPG GdeDqda, hgh aj efJUa GdWQjb Hjf GdeWqhd hGdhSjW, jWeM Gdi GdJfSjb Hjf JbOje JGe LOkG ddbGfhf GdhVYj hGdbGfhfj hGdELJgGOj hGdEQJHGW HGdMdhd GdedehSI ddefWhb GdfXQj GdPj jYWjgG eYfGgG hdeOGgG hMOhOgG hgPG GdcJGH bSe Gdi KdGK CLRGA HOC ef GdYbhO GdfGbdI ddedcjI (B12 (3Gdi (B289 (3Ke JdGg GdLRA GdKGfj GdYbhO GdeJYdbI HGSJYeGd GdGehGd (B300(3Edi (B461 (3Ke GdLRA GdKGdK YbhO GdNOeGJ (B470(3Edi (B811 (3hGdLRA GdQGHY cGf Ydi ZbhO GdGYJeGO (B820(3Edi (B906 (3hCNjQG GdLRA GdNGeS YbhO GdZQQ (B920(3Edi (B1023s
Keywords: (3GdYbhO GdNGUIs; (3bGfhf eOfjs